KEWENANGAN MENTERI.KEUANGAN DALAM.MENGAJUKAN PERMOHONAN PAILIT BUMN - Rahma Widya Swastiningsih; Endang Prasetyawati (Gapenas Publisher, 2022)
State Owned Enterprises (SOE) are the state’s mediator that is expected to be able to achieve their initial goals as agents of development. However, such goals are often difficult to achieve because they are too costly. SOE’s performance is considered inadequate. It only delivers an insignificant impact which could lead to bankruptcy. This study examines how SOE bankruptcy arrangements are executed and what the authority of the minister of finance in submitting bankruptcy applications are. This study1uses a normative juridical method with a conceptual statutory approach to approach SOE bankruptcy arrangements in Law Number 37 of 2004 Article 21paragraph (5). The object in this study is Merpati Nusantara Airlines Ltd. The study found that only the finance minister is entitled to file a bankruptcy action for an SOE engaged in the public interest based on the elucidation of Article 2 paragraph (5) of Law Number 37 of 2004 regarding the authority to file a bankruptcy. In Law.Number 19.of 2003 concerning State-Owned Enterprises, in contrast to state-owned enterprises, whose capital is divided into shares, a public company is defined as a company whose capital is wholly owned by the state and is not divided into shares. All or at least 51%.are owned.by the state. Tge Supreme Court Decision Number: 447 K/pdt.sus-pailit/2016 rejected Sudiyarto and Jafar Tambunan's appeal. The judge's considerations rejected the appeal because the applicant was not entitled to file for bankruptcy. According to the judge, only the finance.minister can apply for bankruptcy